Factors Affecting to Goods Purchasing Decision by using QR Code Transactions of Nakhon Pathom Rajabhat University Students - Puapornpong et.al, Tanatip (Journal of Management Science Nakhon Pathom Rajabhat University, 2019)
This paper aimed (1) to compare purchasing decision with QR Code of undergraduate students in Nakhon Pathom Rajabhat University, categorized by individual factors, (2) to study how marketing mix affecting purchasing decision with QR Code of undergraduate students in Nakhon Pathom Rajabhat University and (3) to examine an influence of attitude and trustworthiness of undergraduate students regarding purchasing decision with QR Code in Nakhon Pathom Rajabhat University. The paper was a quantitative research, examined with 400 samplings from undergraduate students in Nakhon Pathom Rajabhat University. These samplings were collected by convenience sampling technique through a questionnaire-based survey. As the analysis included Percentage, Mean, Standard Deviation, Pearson’s Correlation and Multiple Regression Analysis. The results showed that 1. the gender effected on purchasing decision with QR Code of undergraduate students in Nakhon Pathom Rajabhat University, 2. The marketing mix affects purchasing decision with QR Code. These were dominated by Product (b=0.29), Promotion (b=0.20), Place (b=0.10), and Price (b=0.09) respectively. The predictive power was at 73 percent and multiple regression equation was shown Y = 1.30 + 0.29 X1 + 0.09 X2 + 0.10 X3 + 0.20 X4 3. The attitude and trustworthiness of undergraduate students affects purchasing decision with QR Code was dominated by trustworthiness (b=0.37) and attitude (b=0.26) respectively. The predictive power was at 69 percent and multiple regression equation was shown Y = 1.55 + 0.26 X5 + 0.37 X6 Article history : Received 4 July 2019 Revised 20 July 2019 Accepted 22 July 2019 SIMILARITY INDEX = 0.00